The Relationship Between Cambodian EFL Students’Attitudes Towards Cooperative Learning Strategies and Their Academic Achievement - Hanrith Nou; Sarom Mok; Sothea Lim (Jurnal Educatio FKIP UNMA, 2026)
The Cambodian Ministry of Education, Youth, and Sport (MoEYS) prioritizes three key outcomes: enhanced academic achievement, positive student attitudes, and the adoption of cooperative learning as a core pedagogical approach. While previous research in developing countries has explored the field, such as often featured limited sample sizes and short durations, necessitating further research to bridge these gaps. Accordingly, this study investigates the relationship between students’ attitudes toward cooperative learning and academic achievement within the context of New Generation School (NGS) in Cambodia. This explanatory sequential mixed-methods research design was employed to address the research objectives. The convenient sample comprised 422 NGS students from grade 7 and grade 10. Additionally, three teachers and five students were purposefully selected for semi-structured interviews. Data collection instruments included the research for data were of a five-point Likert scale questionnaires and interview protocols, synthesized and developed by this researcher. Quantitative data were analyzed using descriptive and inferential statistics via Statistical Package for the Social Sciences program (henceforth, SPSS), while qualitative data were processed through content analysis. Main Findings: The findings revealed that the NGS students in both grade 7 and 10 possess highly positive attitudes toward cooperative learning, as measured by the ABC (Affective, Behavioral, and Cognitive) model. These attitudes are rooted in the students’ attitudes towards cooperative learning focuses on its value and benefits. Participants particularly valued cooperative learning for its contribution to social and cognitive development, stress reduction, enjoyment, and learning performance, all of which ultimately contribute to better educational outcomes. However, they had some concerns, including time-consuming, conflicting interests, and potential grade drawbacks in terms of their final course grade. Furthermore, Grade 10 students exhibited more favorable attitudes and higher achievement scored compared to grade 7 students. Statistical analysis a significant difference between the two grade levels regarding their emotional engagement with cooperative learning (p = 0.000). Regarding perceived academic performance, the significance value was 0.011 (at the p < 0.05). Qualitative data further confirmed that teachers perceived cooperative learning as valuable instructional strategy fostering students engaged and motivated. The study recommends the broader implementation of cooperative learning frameworks in classrooms and the transforming of educational institutions into learning communities. The study revealed that cooperative learning improves social skills, cognitive growth, and stress reduction, but students are also concerned about efficiency and fairness in grading. Accordingly, this study shed light on the practical and emotional problems of cooperative learning that were generally missed in the literature. The findings would also provide a more complete knowledge of cooperative learning's adoption in education by bridging theoretical advantages and real-world student concerns.